(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Supernumerary tooth is one that is additional to the normal series and can be found in almost any region of the dental arch .Mesiodens is the most common type of supernumerary tooth found in the premaxilla between two central incisors. They may be single, multiple, unilateral or bilateral, erupted or unerupted in one or, both jaw. It usually results in oral problems such as malocclusion, food impaction, poor aesthetics, and cyst formation. Early diagnosis and treatment is suggested to prevent orthodontic and pathologic complications. This article highlights the orthodontic management of a case of twenty five year old Bangladeshi male with two supernumeraries- one is a supplemental tooth erupted in the oral cavity causing malocclusion and another impacted mesiodens near the nasal floor. The case was managed by a joint effort of maxillofacial surgeon and orthodontist. At first, maxillofacial surgeon removed the two supernumerary teeth. After healing the orthodontic correction was done with fixed appliance using multiloop edgewise technique. It took nearly 18 months to complete the treatment. The patient was happy with the new appearance and function. DOI: http://dx.doi.org/10.3329/bjodfo.v2i1.16002 Ban J Orthod & Dentofac Orthop, October 2011; Vol-2, No.1, 30-33